Developing small and medium-sized enterprises as learning organisations - Hashim, Mohd Khairuddin; Ahmad, Sa'ari (UUM Press, 2011)
Small and medium-sized enterprises (SMEs) need to develop and sustain their competitive advantage is through upgrading their skills and knowledge. Small and medium-sized enterprises can acquire the skills and knowledge that can make them become more competitive as well as innovative by becoming learning organizations. However, the literature indicates that limited attempts have been made to use the concept of learning organization as a way of developing SMEs. This paper initiates an attempt to describe and explain how SMEs can be developed as learning organizations.